2017
DOI: 10.17850/njg97-1-01
|View full text |Cite
|
Sign up to set email alerts
|

A flexural isostasy model for the Pleistocene evolution of the Barents Sea bathymetry

Abstract: The topographic relief of the Barents Sea was subjected to major changes during the past 1.5 million years mostly due to sediment redistribution driven by glacial activity. This paper addresses the problem of Pleistocene bathymetric evolution of the southern Barents Sea using a numerical modelling approach that considers the influence of regional isostasy on relief development. The model presented in this work shows that most of the bathymetric features were initiated prior to the first documented, shelf-edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…This shows that the combination of regional mass-balance studies and more local studies from well data is useful to capture the spatial variation of glacial erosion reflecting the dynamics of the Barents Sea Ice Sheet. Zieba et al (2017) modelled early Pleistocene bathymetry of the southwestern Barents Sea area and found it to have been close to sea level with some areas elevated to about 300 m. Their result is in conformity with and refine previous results suggesting that the Barents Sea was at or near sea level or even partly subaerially exposed prior to glaciation (e.g. Vorren et al, 1991;Butt et al, 2002 and references therein).…”
Section: Estimates Of the Glacial Erosionsupporting
confidence: 87%
“…This shows that the combination of regional mass-balance studies and more local studies from well data is useful to capture the spatial variation of glacial erosion reflecting the dynamics of the Barents Sea Ice Sheet. Zieba et al (2017) modelled early Pleistocene bathymetry of the southwestern Barents Sea area and found it to have been close to sea level with some areas elevated to about 300 m. Their result is in conformity with and refine previous results suggesting that the Barents Sea was at or near sea level or even partly subaerially exposed prior to glaciation (e.g. Vorren et al, 1991;Butt et al, 2002 and references therein).…”
Section: Estimates Of the Glacial Erosionsupporting
confidence: 87%
“…The uplifted Barents Sea region (Dimakis et al, 1998;Faleide et al, 2008) subsequently became the site of nucleation of very large ice masses during several glaciations (e.g., Eidvin et al, 1993). Butt et al (2002) and Zieba et al (2017) based on numerical modeling, suggested that the Barents Sea was subaerial during the earliest Late Pliocene, becoming a submarine platform around ∼1 Ma ago. Both the preglacial and glacial history is reflected in the present-day topography of the Barents Sea region (e.g., Faleide et al, 1996;Ottesen et al, 2008;Andreassen and Winsborrow, 2009;Laberg et al, 2012).…”
Section: Regional Settingmentioning
confidence: 99%
“…1) was nearly the same during NHG phases II and III, implying a change in KBSIS erosion capacity since 0.78 Ma. This reduced erosion capacity may be a consequence of the fact that the Barents Sea at this time was below current sea level (Zieba et al, 2017) and that the KBSIS became a fully marine-based ice sheet.…”
Section: Euris Reconstructionmentioning
confidence: 99%
“…At the end of the Neogene, the paleo-EurIS marine margin was dominated by fluvial sediment input and nonglacial environments. The Barents Sea, which during the entire Cenozoic was subject to uplift, was at this time subaerially exposed, and it is assumed that rivers followed the incipient track of the large troughs that characterize the present-day bathymetry (Vorren et al, 1991;Fjeldskaar and Amantov, 2017;Zieba et al, 2017). At the mid-Norwegian margin, a 600-km-long and as much as 500-mthick and 60-km-wide siliciclastic delta, represented by the Molo Formation, was developing (Eidvin et al, 2007), whereas in the southern and central North Sea, which since the Late Cretaceous has undergone subsidence, rivers built out huge deltas in the late Neogene (e.g., Patruno et al, 2020).…”
Section: Quaternary Development Of the Euris Marginmentioning
confidence: 99%